Funcionamiento familiar y habilidades sociales en adolescentes - Carranza Camus, Kelly Marilyn (2014)
This research study type Quantitative Correlational, cross section was performed in a group of 50 teenagers of the National Comprehensive Family Welfare (INABIF), in 2010, in order to determine the relationship between the type of family functioning and the level of social skills in adolescents. Data were collected through the application of two structured tests, one on the level of social skills and the other on the level of family functioning. The results were processed using SPSS version 15 for Windows and presented in tables and duplicate entries in a numerically and percentage. To determine the relationship between the two variables the chi-square test statistic was used, leading to the following conclusion: There is significant relationship between the level of social skills and the level of family functioning.